Guru Berkarakter Untuk Pendidikan Karakter - Wiwin Luqna Hunaida (Budapest International Research and Critics University, 2017)
A teacher is one of the figures who will serve as role models in their behaviors, actions and saying by the students either in the classroom, school and even outside the school environment or in society. He/She will always be noticed and become a spotlight by his/her surrounding commu- nities. Teachers not only have a job to teach, but also have a duty to educate their country. It means that their noble task is not only to educate children intellectually an sich, but also to instill the noble values as the role models and guidance in livelihoods, whether it is derived from the religious, customary and cultural values, so that they grow as the next generation with high quality of personality and character. To realize these expecta- tions, the teacher must have intellectual abilities and good emotional and spiritual character.